The Influence of Different Configurations and Spacings on the Performance of Oscillating Wave Surge Converters When Operating in Wave Farms - Benites-Munoz, D; Thomas, G; Huang, L (American Society of Mechanical Engineers: ASME, 2022)
Ocean wave energy is significant and permanent, but it is extremely challenging to capture it efficiently using energy conversion technologies. Thus, research on these technologies and the hydrodynamic response of energy devices is constantly growing. One way of increasing the energy extracted from the ocean is to deploy wave farms consisting of arrays of wave energy devices; however, this is not as straightforward as extending the hydrodynamic response of one device. When the incident wavefield interacts with one device, it will be disturbed/modified by its presence, showing behaviours such as reflection, diffraction, and radiation. This perturbed wavefield will interact with neighbouring devices, and its influence can be beneficial or disadvantageous depending on the hydrodynamics. The q factor is commonly used to assess this interaction, which compares the power capture of a wave farm to that of the sum of the same number of devices performing in isolation. In this work, the q factor of configurations of three Oscillating Wave Surge Converters (OWSC), varying the spacing and arrangement, is predicted using Computational Fluid Dynamics. This resulted in beneficial layouts of three devices in different wave conditions, and the optimal array can be extended to numerous devices, which can be applied to the design of wave farms.